Evaluation of distribution of presbyopic correction through primary healthcare centres in Zanzibar, East Africa. Issue 6 (25th February 2011) - Laviers, H; Burhan, I; Omar, F; Jecha, H; Gilbert, C
Abstract : Aim: A pilot scheme was developed to integrate the distribution of ready-made near spectacles into primary eye-care delivery in six primary healthcare facilities in Zanzibar, East Africa. With the aim of scaling it up to national level, the scheme was evaluated in terms of relevance, effectiveness, equality, sustainability and replicability. Methods: Six medical officers were trained in ocular anatomy, history taking, blindness definitions, ocular abnormalities, preventable blindness, distance visual acuity, near visual acuity, eye examination, record keeping and referral criteria. Each clinic was supplied with 200 near spectacles. The evaluation team revisited the units 6 months later to assess the scheme. Results: The evaluation team recommendations included: a structured approach to planning from the outset, facility selection criteria, raising awareness through community meetings, funding through a revolving fund and the introduction of referral monitoring systems. 372 of the 574 patients attending the facilities had eye complaints; 285 eye infections, 29 distance vision problems and 173 near vision problems. 173 near vision spectacles were dispensed, and 74 people were referred. All medical officers and participants recommended continuing with the scheme. Conclusions: The project is highly relevant and timely, given that presbyopia is now a priority with the WHO. The scheme could easily be adopted at the national level in Zanzibar and other areas in East Africa.